نتائج علاج كسور عنق الفخذ داخل المحفظة عند المسنين( بعد سنة - سنتين) عن طريق استبدال المفصل الجزئي (Bipolar) - حلوم, غياث (Latakia University Journal -Medical Sciences Series, 2017)
شملت الدراسة  مريض, تم متابعتهم لمدة سنتين متواصلتين. تراوح عدد الإناث  مريضة بنسبة مئوية  %, تراوح عدد الذكور مريض بنسبة  % . نسبة الإصابة بهذه الكسور عند النساء أكثر من الرجال بنسبة / وخاصة في العقدين السابع والثامن حيث نلاحظ سيطرة النتائج الجيدة عند الإناث. يحدث الضعف العضلي بعد الجراحة بسبب قلة الاستخدام, ويستمر الضعف العضلي لفترة عامين بعد الجراحة مما يقترح استعمال التمارين لفترة طويلة 0هناك تحسن ملحوظ بعد مرور سنتين على العمل الجراحي لكسور عنق الفخذ داخل المحفظة من حيث النتائج السريرية والشعاعية, بالإضافة إلى تحسن في الفعاليات اليومية الروتينية (الوظيفية) للمريض مقارنة مع نفس الشريحة من المرضى بعد مرور سنة على العمل الجراحي.يعتبر التدبير الباكر والحركة الباكرة ماأمكن لتقوية عضلات الطرفين السفليين وتحسين حركة المفاصل المجاورة, غياب الاذيات المرافقة, فترة الاستشفاء الأقل زمناً, تكنيك العمل الجراحي وتقنياته , العناية الطبية و تشجيع الفعاليات الفيزيائية من أهم العوامل التي ساعدت على تقييم الإنذار والتنبؤ به وبالتالي الحصول على مانصبو إليه من نتائج وظيفية جيدة.The study included 25 patients were followed up for two years joined together. The number of females ranged from 18 patients percentage of 72%, the number of males ranged 7 patients by 28%.The incidence of these fractures in women more than men by 3/1, especially in the seventh and eighth decades where we note in this Study, a good results in females.Muscular weakness occur after surgery due to lack of use, and muscular weakness continue for a period of two years after the surgery, which suggests the use of exercise for a long time .There is a noticeable improvement in two years after the surgery for intracapsul femoral neck fractures within the portfolio in terms of clinical and functional findings, in addition to the improvement in activities of daily routine (functional) for the patient compared to the same segment of the patients one year after surgery.The early treatment and movement as possible to strengthen the muscles of the lower limbs and improve the adjacent joint movement, the absence of lesions associated , the period of hospitalization least for so, technique of surgery, medical care and physical activities encourage are the most important facturs that have helped to warning and predictable, then we get agood results as we wont.